Internationalization of Higher Education Cooperatives: Economic, Legal, Health, and Technology Synergy through PKM in Malaysia - Handayani, Tuti; Nino Sri Purnama Yanti; Gusmawet; Nurhayati; Oktavianis; Resty Noflidaputri (Journal of Community Service and Application of Science, 2025)
International community service (PKM) is a tangible manifestation of the involvement of universities in bridging science with practice in the field across countries. This activity was carried out through a mock study and collaboration between Indonesian Higher Education Cooperatives and cooperative institutions in Malaysia, involving economic, legal, health, and technological aspects. "The partners of international PKM activities are the Universiti Malaya Alumni Cooperative (KAGUMI) and the Universiti Teknologi MARA Cooperative (UiTM), with the support of the ANGKASA federation as the Malaysian national cooperative organization." The purpose of the activity is to strengthen the institutional capacity of higher education cooperatives in facing the era of globalization and increase the competitiveness of members at the regional level. The methods used are in the form of Focus Group Discussion (FGD), institutional visits, observation of cooperative practices in the field, and the preparation of multidisciplinary-based action plans involving the fields of economics, law, health, and information technology. The results of the activity show that the internationalization of university cooperatives can be carried out through strengthening cross-border networks, the application of cooperative governance principles based on modern law, the use of digital technology for marketing and administration, and the development of value-added local health and economic products. In conclusion, this international PKM opens up opportunities for academic and practical synergy that are able to expand the role of higher education cooperatives in sustainable development, expand ASEAN cooperation networks, and support the role of academics as agents of transnational change.